프로젝트 학습의 도덕교육에의 적용 -「2012 도덕과 교육과정」에 따른 『생활과 윤리』 생명윤리 수업을 중심으로 - 이경희; Kyung Hee Lee (윤리연구, 1(99), 2014)
창의성과 협력, 소통, 존중, 배려, 공감이 근간이 되는 정보사회와 다문화사회에서의 교육은 교사가 주도하는 교과서 중심의 이론 수업과 주입식 방법만으로 그 효과를 기대할 수 없다. 「2012 도덕과 교육과정」은 학생 스스로 주제를 선택하고 교육과정을 설계하며 소집단 활동을 통해 토의, 현장 활동, 표현, 조사, 전시를 통해 체험ㆍ탐구하는 프로젝트 접근을 인성교육의 학습방법으로 추가하여 자기주도적 학습을 강조하고 있다. 프로젝트 접근은 도덕과 선택과목 『생활과 윤리』가 제시하고 있는 교육목표, 즉 학생들이 현대생활의 제 영역에서 발생하는 다양한 윤리 문제들을 주도적으로 탐구하고 성찰함으로써 인간과 세계를 윤리적인 관점에 비추어 올바르게 이해하고, 도덕적 판단력 및 의사결정 능력을 함양하며 공동체 안에서 도덕적 삶을 실천할 수 있는 인성을 성취하는데 적합한 교육방법이다. 본 논문에서는 프로젝트 학습을 생명윤리 수업에 적용하여 교사의 안내와 학생의 주도적 실천으로 교육효과를 극대화시키는 ‘교육과정의 재구성’을 시도하고 있다. The existing textbook-based education that is initiated by teachers is unable to meet the demand of information society requiring creativity and that of multi-cultural society constituting the basis of cooperation, communication and consideration. According to 「2012 Curriculum」, an project approach was added, as a learning method, by which a student oneself selects the subject, designs an educational course, makes a discussion through small group activities and experiences & researches through site activities, expression, investigation and exhibition. An project approach is a very suitable educational method in achieving the educational goals proposed by the elective subject of morals 「Life and Ethic s」― to properly understand human beings and the world from the ethical viewpoint, improve moral judgment and the ability to make a decision and to cultivate character able to practice moral life within the community by initiatively researching and reflecting over a variety of ethical problems occurring from various areas of modern life. This paper is intended to attempt the possibility of ``re-organization of curriculum`` which leads to maximal education effects through teacher`s guidance and student`s initiative practice by the project approach to the subject of life ethics.